Differences between adult and adolescent male mice in approach/avoidance and expression of hippocampal NPY in response to acute footshock. (2nd November 2021) - Cortes, Mariana A.; Corder, Katelynn M.; Dobrunz, Lynn E.
Abstract: Anxiety disorders are the most common neuropsychiatric disorders diagnosed in adolescence and adulthood. Stress can lead to an increase in anxiety-related behaviors, although the consequences of stress in rodents are typically investigated only in adults. The levels of Neuropeptide Y (NPY), a mediator of stress resilience, are reduced in adult patients with Post-Traumatic Stress Disorder. For rodents, footshock is a physical stressor that increases anxiety-like behavior and reduces NPY in adults, however, the effects in adolescents are unknown. Here we used a 30-min unpredictable footshock protocol to investigate the differences in behavior and stress-relevant molecules between adolescent (6 weeks) and adult (3 months) male C57Bl6/J mice. The protocol resulted in fear expression in both ages as observed by enhanced freezing during footshock and elevation in plasma corticosterone and NPY shortly after exposure. However, effects on approach/avoidance behavior were different between the two ages. One week after footshock exposure, adult mice showed reduced open arm time and entries on elevated plus maze (EPM), whereas adolescent mice showed no effect. Footshock mice in both age groups displayed reduced activity levels in EPM and open field. The hypolocomotion did not relate to motor deficits, as there were no differences between footshock and control groups using rotarod. Surprisingly, we found that the adolescent mice had elevated NPY peptide expression in hippocampus, whereas adults had reduced expression one week after footshock exposure. Together, these results demonstrate that stress differentially affects both behavior and the important stress resilience factor NPY in adolescents compared to adults.